Time to recovery from moderate acute malnutrition and its predictors among children aged 6–59 months in Fedis Woreda, East Hararghe Zone, Eastern Ethiopia - Melaku, Berhanu; Gebremichael, Berhe; Negash, Belay; Kitessa, Monas; Kassa, Obsan; Dereje, Jerman; Kefelegn, Reta; Firdisa, Dawit (Frontiers in Nutrition, 2024)
Background: Acute malnutrition is a major global public health problem, particularly in low-and middle-income countries. A targeted supplementary feeding program is an approach recommended to address moderate acute malnutrition in food-insecure settings. Preventing and treating moderate acute malnutrition requires identifying factors shown to affect the treatment outcome and duration of stay on treatment. This study aimed to determine the time to recovery from moderate acute malnutrition and its predictors among children aged 6-59 months in Fedis Woreda East Hararghe